Evaluation of wind energy potential at four provinces in Morocco using two-parameter Weibull distribution function - Abdelaziz Ait Sidi Mou; Lahcen Ait Naceur; Mohammed Daoudi (Institute of Advanced Engineering and Science, 2022)
In the last years, the use of wind turbines for power generation has increase due to the advance's technology used and the stable cost. In this paper, due to the low investment in the desert regions of Fezouata, Ouijjane, El Ouatia, and Taroudannt in Morocco, we have considered wind resources as an ideal option. Using meteorological statistics, Weibull's distribution function was able to estimate the wind power and potential of four various wind turbines for each site with various nominal powers, ranging from 250 kW to 2000 kW, for use in wind farms. 24 years of wind speed data to fit the Weibull distribution. For the four provinces examined, the annual mean value of wind speed and frequency distributions were collected. The desert province of El Ouatia shows that it is economically feasible to install a wind farm for the production of green energy.